Two new species of Elachistocleis Parker, 1927 (Anura: Microhylidae: Gastrophryninae) from Colombia - Acosta-Galvis, Andrés R.; Tonini, João F. R.; de Sá, Rafael O. (Zootaxa, 2022)
The genus Elachistocleis consists of small to medium size species of Neotropical microhylids. It is the second largest genus of New World microhylids and an important component of the anuran diversity in the Neotropical region. Herein, based on morphological, acoustical, and molecular evidence, we describe two new species and their advertisement calls. The new species have reticulated venter and inhabit the Orinoco basin of Colombia.